Does monopsony exist in academic labor market? - Yunisvita Yunisvita (Jurnal Ekonomi Pembangunan, 2020)
This study aims to examine empirically the power of monopsony in the academic labor market, particularly in public universities. Upward sloping supply curve is indicative of monopsony and its power supply elasticity is suspected of demand for lecturers. The method used to estimate the supply equation for lecturer at four public universities in Indonesia is OLS model. A stratified sample is determined proportionally as much as 348 lecturers, by academic rank, gender and discipline. It is found that the supply elasticity is inelastic indicating that earnings lecturers are in non-competitive conditions. When employers face an inelastic supply curve, the marginal expenditure and average expenditure is very much different, which gave it the power to set wages, so it implies that the power of monopsony is big.